2012
DOI: 10.31436/iiumej.v12i5.233
|View full text |Cite
|
Sign up to set email alerts
|

Modification of ITU-R Rain Fade Slope Prediction Model Based on Satellite Data Measured at High Elevation Angle

Abstract: Rain fade slope is one of fade dynamics behaviour used by system engineers to design fade mitigation techniques (FMT) for space-earth microwave links. Recent measurements found that fade slope prediction model proposed by ITU-R is unable to predict fade slope distribution accurately in tropical regions. Rain fade measurement was conducted  in Kuala Lumpur (3.3° N, 101.7° E) where located in heavy rain zone by receiving signal at 10.982 GHz (Ku-band) from MEASAT3 (91.5° E) on 77.4° elevation angle. The measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…0.2 mm tipping-bucket rain gauge is integrated in the system and logged every 10s time interval to measure rainfall rate and determine rainy events. System elaboration can be found in [4].…”
Section: Experimental System and Data Processmentioning
confidence: 99%
See 1 more Smart Citation
“…0.2 mm tipping-bucket rain gauge is integrated in the system and logged every 10s time interval to measure rainfall rate and determine rainy events. System elaboration can be found in [4].…”
Section: Experimental System and Data Processmentioning
confidence: 99%
“…Average fade duration is a ratio of annual accumulated time duration T tot to annual number of occurrence event N tot at a given fade threshold as presented in (3) (4) Fade duration is analysed based on two data sets such as filtered and unfiltered data. Unfiltered data is noticeably shown that it has higher number of events and exceedance times than filtered data.…”
Section: Average Fade Durationsmentioning
confidence: 99%
“…Raining events were manually removed based on 0.2 mm tipping bucket rain gauge which is time synchronized measurement. Details of the experimental setup are available in [4,5].…”
Section: Experimental Setup and Data Processingmentioning
confidence: 99%
“…Video streaming was performed over a high-speed link via the WINDS satellite in a tropical area (Singapore) to investigate the effects of rainfall on the signal strength of the link and the video quality [11]. The rain induced scintillation was studied based on attenuation measurement over a one year period during 2011 and 2012, from MEASAT3 satellite at Ku-band (12)(13)(14)(15)(16)(17)(18) in Malaysia [12]. In [13], the performance of the Silva Model in [14] for rain attenuation prediction in slant paths for satellite links was investigated and compared to the ITU-R P.618-11 model [15] based on data from three slant paths in tropical regions of Malaysia [16], [17] and Australia [18].…”
Section: Introductionmentioning
confidence: 99%